Peran Kegiatan Ekstrakulikuler Pramuka dalam Mengembangkan Karakter Mandiri Siswa SD Plus bakti Nusantara 666 - Aulia Nur Jannah; Delia Maharani; Latifah Meynawati; Putri Salma N (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The study of the background with the student at clean-up elementary school has not yet formed his character, it can be seen from the student doing his duty to see his friend, cleaning the class being told by the teacher. The purpose of this study is to describe the independent character education through extracurricular scout activities at devotion nusshal elementary school, which is between 666 and its support factors and constraints. It is a qualitative descriptive study. Research subjects are principals and extracurricular scouts. Data collection through observation, interviews, and documentation. The results of this study explain that the implementation of extra-curricular scout activities can establish a student's independent character is seen in the self-reliance attitudes of each student based on the regular exercise and camp exercises. To the performance of independent character education in extracurricular activities the self-forming self-help group of self-supporting values includes confidence, responsibility, hard work, being able to make decisions, being able to work alone, and respecting time.